Effect of Fortification of Chocolate Seaweed (Sargassum sp.) on Quality Characteristics of Goat's Milk Ice Cream - Dahlia Dahlia; Dewita Dewita; Yance Gusriyanti (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
This study aimed to determine the quality characteristics of goat's milk ice cream with fortified brown seaweed (Sargassum sp.). The research method used was a non-factorial completely randomized design (CRD) with 4 levels of treatment, namely R0 (0% Sargassum sp.), R1 (5% Sargassum sp.), R2 (10% Sargassum sp.), R3 (15% Sargassum sp.). The test parameters carried out were organoleptic quality analysis of appearance, aroma, taste, and texture. The results showed that goat's milk ice cream with fortified brown seaweed (Sargassum sp.) had a significant effect on the chemical and physical quality characteristics at the 95% confidence level. The value of the chemical and physical quality of the best treatment was R3 (15% Sargassum sp.), with a moisture content value of 63.06%, a crude fiber content value of 1.65%, the value of calcium content 1.74%, melting time value is 24.47 minutes, and viscosity value is 252.10 cPs.